Application of Monte Carlo simulation codes to plan an activation experiment in Scandium-45 targets - Costa, Pedro (2014)
Data characterizing excitation functions of nuclear reactions are necessary for different applications, with the process of radionuclide production being assumed as a relevant example. This is the only way to define and optimize technical parameters involved in such a process. However, nuclear activation experimental studies are sometimes difficult to implement, and care should be taken before its execution, in order to obtain all relevant data, while correctly planning the experiences. In this context, Monte Carlo simulation tools are widely applied to overtake such difficulties. This work describes a case-study aiming to characterize nuclear reactions excitation functions induced by a proton beam and its interaction with a Scandium target – a specific situation that is not yet completely characterized and that might be of relevance, since it could be useful to produce medically relevant radionuclides (eg. Titanium-45).